N-Pyrrolidine-based α/β-peptides incorporating ABOC, a constrained bicyclic β-amino acid, for asymmetric aldol reaction catalysis. Issue 13 (31st March 2016) - Milbeo, Pierre; Maurent, Kelly; Moulat, Laure; Lebrun, Aurélien; Didierjean, Claude; Aubert, Emmanuel; Martinez, Jean; Calmès, Monique
Abstract: A series of N -pyrrolidine-based α, β-peptide catalysts incorporating a constrained 2-aminobicyclo[2.2.2]octane carboxylic acid (ABOC) residue were synthesized and evaluated in the asymmetric aldol reaction from acetone and some p -substituted benzaldehydes. Their catalytic properties were shown to be highly dependent on the amino acid sequences and on the absolute configuration of the ABOC residue that played a determinant role. Among the peptides tested, the heterochiral tripeptide H-Pro-( R )-ABOC-Asp-OCH3 13, that adopts a turn conformation in the solid state, proved to be the most efficient catalyst affording β-hydroxy ketones in high yields and good enantioselectivities (up to 87%). Graphical abstract: